Assessing neurotropic effects of new antiepileptic nitrogen-containing drugs - R. G. Paronikyan; G. G. Avakyan; V. N. Avakyan; E. G. Paronikyan (Эпилепсия и пароксизмальные состояния, 2023)
Objective: to evaluate an effectiveness of new nitrogen-containing compounds for alleviating epileptiform conditions in animal experimental study, and conduct molecular modeling of a new neurotropic drug.Material and methods. The anticonvulsant and psychotropic effects of six new heterocyclic compounds synthesized at the Institute of Fine Organic Chemistry were analyzed: № 1 (tetrahydrobenzothienopyrimidine), № 2 (pyridopyrimidine), № 3 (pyranotriazolopyridine), № 4 (thioalkylpyranotriazolopyridine), № 5 (pyrazolyltetrahydrothienoisoquinoline), and № 6 (thioxopyranopyridine). Experiments were carried out with 300 white outbred male mice weighing 18–24 g and 48 male rats weighing 120–150 g. The anticonvulsant spectrum of action was assessed in mice using the following tests: maximum electric shock, corazole-induced seizure. The psychotropic compound-related properties were analyzed using the following tests: elevated plus maze, open field, conflict situation. The neurotoxic compound-related effects were evaluated by incoordination of movements in rotating rod test. Comparison was performed with pufemide (3-(p-isopropoxyphenyl)succinimide), ethosuximide and diazepam.Results. The new nitrogen-containing drugs were revealed to exhibit high anticonvulsant activity, especially observed in corazoleinduced seizure test. All select compounds have anticonvulsant, anxiolytic, psychosedative or behavior-activating effects. Compound № 1 (N3212) is the most effective (median effective dose is 16 mg/kg) in antagonism to corazole action and is significantly superior to ethosuximide and pufemide exceeding by 10- and 5-fold, respectively. The compound shows least toxic (median lethal dose is 2300 mg/kg) and low neurotoxic (median toxic dose is 660 mg/kg) effects. Therapeutic and protective indices for Compound No. 1 exceeds that of ethosuximide by 17- and 13-fold, and of pufemide by 6- and 8-fold, respectively.Conclusion. The select compounds are superior to the approved drugs used in medical practice, pufemide and ethosuximide. A Compound N3212 selected among them may find application as an anticonvulsant drug with psychotropic effects.